LISSI comics as thematic learning media for literacy in elementary school students - Alifah Fatikhatun Nafisyah; Fina Fakhriyah; Mohammad Syaffruddin Kuryanto; Mohamed Nor Azhari Azman; Dewi Fatmawati (Research and Development in Education (RaDEn), 2023)
As a result of the Covid-19 pandemic causing several problems in the world of education. One of them is the reduced knowledge and skills of students, namely literacy habits, especially in reading-writing literacy and the lack of use of digital media in the current era. The purpose of this study was to prove the effectiveness of LISSI comics as thematic learning media for literacy in grade 3 elementary school students. The research was conducted using a quasi-experimental method with a one group pretest-posttest design. The research subjects used were grade 3 students at SD N 2 Ringin and SDN 1 Sendangmulyo, Rembang district. The results of the calculation of the Paired Sample T-test show that each data gets a sig. = 0.00, this shows that there are differences in students' literacy skills before and after using LISSI comics. And the N-gain results show an increase in students' abilities. Based on the final results obtained, LISSI comics were declared effective so that they were suitable for use as learning media as well as supporting literacy for third grade elementary school students.